(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
Attending school classes has an important role in education. It is the opportunity of the students to acquire knowledge and enhance their skills. Nowadays, our school system is facing different problems and challenges that affect the student’s particular life. One of these is the absence of a student to his or her class leading to dropouts. This is the reason why there is a large number of undergraduates in our country. The goal of the researchers is to determine the causes and effects of absenteeism and to develop policies and give recommendations to prevent and lessen the effects of this problem. A descriptive method design was used in the study. We utilized the purposive sampling technique to eighty-five (85). The target population includes those who incurred more than 5 absences from their classes. Questionnaires and unstructured interviews are the instruments used to gather data from freshmen students in the College of Teacher Education. It includes a set of specific questions to formulate a specific response to answer the causes and effects of absenteeism among freshmen students. 85 freshmen students in the College of Teacher Education participated in the survey. The majority of them are female students ranging from 18 to 20 years old. The result of the study revealed that factors such as personal, peer, family, health and teacher-related factors cause absenteeism to the students. “Not interested in school, influenced friends, unconcerned parents, fever, and didn’t like the teacher” are common reasons why students are absent from their class. It is hard for students who have chronic absences to focus on their studies and understand the lesson of their teacher. They failed to comply with their requirements needed and also failed in quizzes and major exams. There is a need to motivate students to attend regularly in their classes. Teachers and parents as well should monitor the attendance of their children and, if possible, should have open communication with each other. The school has provided many ways and means to minimize if not eliminate absences.